2018
DOI: 10.1097/mpg.0000000000001688
|View full text |Cite
|
Sign up to set email alerts
|

Rising Incidence of Paediatric Inflammatory Bowel Disease in Canterbury, New Zealand, 1996–2015

Abstract: The incidence of paediatric IBD in Canterbury has increased dramatically during the last 2 decades. Some of the observed incidence rates are among the highest documented anywhere in the world. The preponderance of CD over UC in the present study is the highest published.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
52
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(57 citation statements)
references
References 26 publications
4
52
1
Order By: Relevance
“…Large‐scale population‐based studies on pediatric patients with IBD have mostly been reported in Western populations . Over the last two to three decades the incidence rates of pediatric IBD in general has shown a rising trend . Benchimol et al .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Large‐scale population‐based studies on pediatric patients with IBD have mostly been reported in Western populations . Over the last two to three decades the incidence rates of pediatric IBD in general has shown a rising trend . Benchimol et al .…”
Section: Discussionmentioning
confidence: 99%
“…reported that the incidence per 100 000 population in Ontario, Canada, rose from 9.5 to 11.4 between 1994 and 2005 . A recent study from Canterbury, New Zealand, indicated that there was an even higher rise of 4‐fold in the annual incidence rates from 2.88 per 100 000 to 13.06 per 100 000 over a 20‐year period from 1996 to 2015 . Similarly, in northern France, the mean incidence rate of CD increased by 20%; however, that of UC decreased by 17% over a 12‐year period (1988–1999) …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study was limited by the disproportionate distribution of diagnoses among the group of children with IBD, limiting meaningful comparisons between participants with CD and UC and possibly masking any actual difference that may be present. This disparity of numbers, with CD patients being better represented, was universally found among the studies carried out in the paediatric IBD population, which mirrors local [35,36] and worldwide trends [37]. Further studies will be performed to address this and other limitations, in that parent and child comparisons were not made, and generalisability to the wider population of children with IBD was not established.…”
Section: Limitationsmentioning
confidence: 99%
“…The incidence of inflammatory bowel disease (IBD) in children and adolescents is increasing across the globe [1]. High rates of IBD have been shown in New Zealand, with increasing incidence documented [2, 3]. Many reports illustrate that IBD can impact adversely upon the psycho-social well-being of individuals [4].…”
Section: Introductionmentioning
confidence: 99%